Characterization of heating elements of different dimensions used in resistance welding of thermoplastic matrix composite materials - Öztürkmen, Hakan; Usta, Yusuf; Toros, Serkan; Öztürk, Fahrettin (İdris Karagöz, 2023)
Resistance welding is one of the most useful methods for joining of thermoplastic composite materials. In this method, the joining process between two thermoplastic composite materials by passing a current through a stainless-steel heating element under pressure for a certain period. Within the scope of this study, meshes with a width of 12.7, 25.4, 38.1, 50.8, 63.5, 76.2 mm and a length of 160 mm were used to characterize the joule heating performance. These meshes have a mesh range of 33, 45, 61, 91, 109 and 154 microns. The temperature values on the heating elements were observed with a thermal camera by giving different current values to the relevant elements. Results reveal that the 12.7 x 160 mm heating element with 33-micron mesh spacing reached 349 ? under 10 A current, and the temperature value increased with current. In addition, it was determined that the resistance values of the heating elements with different widths were determined by the relevant system and the resistance properties changed non-linearly with the width.
Keywords: Resource Technologies; Kaynak Teknolojileri